Self-Consistency Congruence and Smartphone Addiction in Adolescents: The Mediating Role of Subjective Well-Being and the Moderating Role of Gender - Li, Yang; Ma, Xiaoqing; Li, Chun; Gu, Chuanhua (Frontiers in Psychology, 2021)
Adolescent smartphone addiction has increasingly attracted the attention of scholars because of the widespread use of internet technology in educational environments. This research was conducted to examine whether subjective well-being would mediate the relation between self consistency congruence and adolescent smartphone addiction, and whether gender would moderate the mediating process. A total of 1011 Chinese adolescents completed self-report questionnaires measuring self-consistency congruence, subjective well-being and smartphone addiction. Self-consistency congruence was shown to be a significant predictor of smartphone addiction. Furthermore, subjective well-being partially mediated the association between self-consistency congruence and adolescent smartphone addiction. Gender could moderate the mediating process. We envision the findings as being helpful in guiding scholars develop interventions for minimizing smartphone addiction in adolescents and its disrupting effects.